SENTRA BATIK SEBAGAI DESTINASI WISATA DENGAN PENDEKATAN KEARIFAN LOKAL DI SURAKARTA - Dwiputra, Reza Septian; Suastika, Made; Sumadyo, Amin (ARSITEKTURA, 2016)
In this modern era, batik fashion has begun to be ignored by the entry of foreign fashion culture that makes clothing in the country is less desirable. With declining public interest in Indonesian culture of batik, the authors took the initiative wants facilitate batik entrepreneurs large and small, to cooperate in preserving and developing batik. Not only provide container, but gave the tourist attractions in batik. So, traveled as well as learn about batik. Containers to be built covers several activities related to batik. Batik is not only in terms of clothing, batik can be applied to the world of architecture such as the application forms of the motif into the building. Implementation into the building that is the basic form, the skin and the elements in buildings. The issue is how to design a form Sentra Batik design by applying the concept of Local Wisdom, which raises the shape of the building with a mix of local culture and foreign culture. The method used is the method of architectural design. The result of the design of a regional architecture concept Sentra Batik with Local Wisdom is applied to the shape of the building as Joglo with a combination of forms of batik motif on building elements.Keywords:Batik, Batik Tourism, Local Wisdom, Sentra Batik.In this modern era, batik fashion has begun to be ignored by the entry of foreign fashion culture that makes clothing in the country is less desirable. With declining public interest in Indonesian culture of batik, the authors took the initiative wants facilitate batik entrepreneurs large and small, to cooperate in preserving and developing batik. Not only provide container, but gave the tourist attractions in batik. So, traveled as well as learn about batik. Containers to be built covers several activities related to batik. Batik is not only in terms of clothing, batik can be applied to the world of architecture such as the application forms of the motif into the building. Implementation into the building that is the basic form, the skin and the elements in buildings. The issue is how to design a form Sentra Batik design by applying the concept of Local Wisdom, which raises the shape of the building with a mix of local culture and foreign culture. The method used is the method of architectural design. The result of the design of a regional architecture concept Sentra Batik with Local Wisdom is applied to the shape of the building as Joglo with a combination of forms of batik motif on building elements.Â Keywords:Batik, Batik Tourism, Local Wisdom, Sentra Batik.